Tinjauan Aksesibilitas Masjid Raya Baiturrahman Banda Aceh bagi Penyandang Disabilitas - Nada Nadhifa; Marlisa Rahmi; Mira Alfitri (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Abstract. Public buildings are formed based on public activities and needs. The building must meet the needs of users as a whole. One of the public buildings most needed by the community is a house of worship. For the people of Aceh, one of the houses of worship that is quite often visited is the Baiturrahman Great Mosque, which is located in the center of Banda Aceh City. The existence of disability issues raises questions about the needs of persons with disabilities which makes this question the basis of this research. The question in this research is how accessible is it in a public building, especially for persons with disabilities. The research method used in this research is descriptive qualitative. Data collection is done by observation. that the results of the study show that the Baiturrahman Grand Mosque in Banda Aceh, has not fully implemented the concept of a disability-friendly building. This is because the availability of supporting facilities for persons with disabilities has not been maximized, and some of the facilities provided cannot be used properly, so that when viewed from the perspective of the needs of persons with disabilities, this building cannot operate optimally.